A surface treatment method for glass

CN122892576APending Publication Date: 2026-10-09HEBEI SHENGGUANG CHENDA TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610830818.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]2.通过化学溶液浸泡在玻璃表面生成纳米厚度的金属氧化物作为黏附层提高电镀铜层的结合力;该方法生成异于玻璃基板组分的氧化物层,易导致电气性能不良

Benefits of technology

本发明在利用激光诱导蚀刻通孔工艺后,又额外进行了金属化预处理工艺,利用特殊配制的预处理液对玻璃晶圆和孔内壁进行表面处理,形成微观结构,增加粗糙度,从而实现了与金属铜附着力的显著提升。本方法能够在传统工艺上进行直接改进应用,整体步骤简单,成本较低,并可显著提高其后续处理的附着力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The application discloses a kind of surface treatment methods of glass, belong to the technical field of glass processing for semiconductor, comprising the following steps: (1) laser-induced treatment: glass is treated by laser-induced, and induced denaturation is carried out to glass by pulsed laser;(2) etching treatment: etching liquid is used to the glass after laser-induced treatment is etched and handled, and etching is reserved after through hole;(3) pretreatment before metallization: the glass after etching treatment is immersed in pretreatment liquid and is handled, during control solution temperature is 25~50 ℃, after 1~20 min of reaction treatment, it is taken out and is reserved;(4) sputtering treatment: Ti adhesion barrier layer and Cu seed layer are deposited to glass surface by sputtering process;(5) electroplating treatment: metallization treatment is carried out using electroplating process.The application increases pretreatment process before metallization, and by controlling etching condition, microstructure is formed on glass surface, to achieve the effect that the bonding force between glass and metal film layer is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor glass processing technology, and specifically relates to a surface treatment method for glass. Background Technology

[0002] As the demand for more powerful computing increases, semiconductor circuits are becoming increasingly complex, making improvements in signal transmission speed, power delivery, design rules, and the stability of packaging substrates crucial. In this context, glass substrates, as a novel solution, offer a smoother surface than plastic substrates and can accommodate significantly more openings within the same area compared to organic materials. Furthermore, glass substrates exhibit superior thermal properties, physical stability, and high-frequency dielectric properties.

[0003] However, in the actual manufacturing process of glass through-hole metallization, due to the smooth surface of the glass, the adhesion of copper is relatively low, which easily leads to phenomena such as metal layer peeling and curling. Currently, there are several ways to improve this: 1. Using ultraviolet light to clean the glass surface to enhance the adhesion between the copper layer and the glass; this method mainly activates the weakly connected hydroxyl groups on the glass surface, thereby increasing the adhesion, but its degree of improvement in adhesion is limited.

[0004] 2. A nano-thick metal oxide layer is generated on the glass surface by immersing it in a chemical solution to improve the adhesion of the electroplated copper layer; however, this method generates an oxide layer with a composition different from that of the glass substrate, which can easily lead to poor electrical performance.

[0005] Therefore, it is particularly important to develop a more efficient and cost-effective processing method. Summary of the Invention

[0006] This invention discloses a glass surface treatment method to enhance the adhesion between glass vias and a metal film. Specifically, after laser-induced etching of the vias, a pretreatment process before metallization is added. By controlling the etching conditions, a microstructure is formed on the glass surface, thereby enhancing the adhesion between the glass and the metal film layer.

[0007] A method for surface treatment of glass includes the following steps: (1) Laser-induced treatment: Laser-induced treatment of glass is performed by using pulsed lasers to induce deformation in the glass. (2) Etching process: The glass after laser-induced treatment was etched with an etching solution to create through holes for later use. (3) Pretreatment before metallization: The etched glass is immersed in a pretreatment solution for surface treatment, during which the solution temperature is controlled at 25~50℃. After the reaction treatment is 1~20 minutes, it is taken out for use. (4) Sputtering treatment: The glass surface after step (3) was prepared by sputtering to deposit a Ti adhesion barrier layer and a Cu seed layer. (5) Electroplating treatment: The glass surface after step (4) is metallized by electroplating.

[0008] Furthermore, the glass is alkali-containing glass or alkali-free glass.

[0009] Furthermore, the components and corresponding mass percentages in the alkali glass are as follows: SiO2: 80-85%; Al2O3: 1.7-2.5%; B2O3: 11.1-14.5%; Na2O: 0.5-5%; clarifier: 0-2%.

[0010] Furthermore, the components and corresponding mass percentages in the alkali-free glass are as follows: SiO2: 60-65%; Al2O3: 16-17.5%; B2O3: 11.1-14.5%; MgO: 1-2%; CaO: 3-6%; SrO: 1-3%; BaO: 0.5-1%; clarifier: 0-2%.

[0011] The reasons for the above-mentioned specific limitations on the composition of glass are as follows: SiO2, as a network forming agent for base glass, can form glass on its own and is an essential component, imparting excellent chemical stability, mechanical properties, and forming properties to the base glass. However, excessive SiO2 also slows down the etching rate of un-induced areas after laser-induced etching, resulting in a conical pore morphology.

[0012] The aluminum-oxygen tetrahedra formed by Al2O3 in glass have a larger volume than the silicon-oxygen tetrahedra, causing the glass volume to expand and thus reducing the glass density. However, Al2O3 is an extremely refractory oxide, which can rapidly increase the high-temperature viscosity of glass, making it more difficult to clarify and homogenize the glass, and greatly increasing the concentration of bubble defects in the glass.

[0013] B2O3 is also a glass-forming oxide. The boron-oxygen tetrahedron [BO4] has a framework structure, which is compact and effectively reduces the dielectric constant. However, if the B2O3 content continues to increase, there will be insufficient free oxygen in the glass, leading to an increase in the layered boron-oxygen trigonal [BO3] structure and a decrease in the boron-oxygen tetrahedron [BO4] content. This results in a loose glass network structure, unstable chemical properties, and increased volatilization due to excessive boron oxide content, which can also easily cause uneven glass composition.

[0014] MgO, CaO, SrO, and BaO are all alkaline earth metal oxides. Their addition can effectively reduce the high-temperature viscosity of glass, thereby improving the glass's meltability and formability. However, excessive content of these oxides will lead to poor glass stability.

[0015] Alkali metal Na₂O is a good flux that can reduce the viscosity of glass and improve its workability. However, the more monovalent cations there are, the looser the structure, the larger the network porosity, and the worse the glass stability.

[0016] Clarifying agents CeO2 and SnO2 improve the melting quality of glass, and are added in small amounts to remove air bubbles from the glass.

[0017] Furthermore, the energy of the pulsed laser mentioned in step (1) is 50uJ~100uJ.

[0018] Furthermore, the etching solution used in step (2) is HF acid or KOH solution, the mass fraction of the solute in the etching solution is controlled at 3%~50%, the etching temperature is controlled at 25~85℃, and the etching time is controlled at 10~600min; after etching, the glass is rinsed with deionized water for 3~5min.

[0019] Furthermore, the pretreatment solution mentioned in step (3) is a mixture of ammonium fluoride, ammonium sulfate and oxalic acid in a mass ratio of 1:1~5:2~6, and the mass concentration of the solute in the pretreatment solution is 20~40%; after the pretreatment solution is prepared, it needs to be aged at room temperature for 40~50 hours before use.

[0020] Furthermore, during the sputtering process described in step (4), the thickness of the Ti adhesion barrier layer inside the glass hole is controlled to be 300 nm, and the thickness of the Cu seed layer is controlled to be 2 μm.

[0021] Furthermore, the composition and content of the copper plating solution used in step (5) are: 40 g / L Cu 2+ 60 g / L H2SO4, 50 ppm Cl 3 mL / L SFT_A, 10 mL / L SFT_S, 5 mL / L SFT_L; the current density is controlled at 0.18 A dm during electroplating. -2 Electroplating time was 30 minutes, then the current density was adjusted to 0.25 A dm. -2 The reprocessing time is 90 minutes.

[0022] The present invention has the following advantages over the prior art: This invention, after utilizing laser-induced etching for through-hole processing, further incorporates a metallization pretreatment process. A specially formulated pretreatment solution is used to treat the surface of the glass wafer and the inner walls of the holes, forming a microstructure and increasing roughness, thereby significantly improving adhesion to metallic copper. This method can be directly applied to improve upon traditional processes, with simple overall steps, low cost, and significantly enhanced adhesion for subsequent processing. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of the embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0024] Example 1 A method for surface treatment of glass includes the following steps: Preparation of the glass substrate: The mass percentages of SiO2: 85%; Al2O3: 2%; B2O3: 12%; Na2O: 4.5%; SnO2: 0.2% were used. Quartz sand, alumina, boron oxide, and tin oxide were weighed and uniformly mixed to obtain a homogeneous batch. The batch was then transferred to a platinum crucible of approximately 1500 ml and placed in a high-temperature furnace with a silicon molybdenum rod. The temperature was gradually increased to 1650℃ and held for 6 hours, with stirring to accelerate the removal of glass bubbles. After melting, the molten liquid was poured into a heat-resistant stainless steel mold for shaping. The glass block was then removed and transferred to a box annealing furnace for heat treatment at 600℃ for 4 hours, followed by natural cooling to room temperature to obtain the base glass. The glass block was cut, ground, and polished to prepare samples of 20 mm × 5 mm × 1 mm.

[0025] Laser-induced etching of through-holes: The glass sample was irradiated with a laser beam of E=55uJ / pulse, pulse width τ=16ps, and repetition frequency f=500kHz. The modified glass sample was then immersed in a 5% HF acid solution and ultrasonically bathed at 30℃ for 30 min, followed by rinsing with deionized water for 5 min.

[0026] Pretreatment before metallization: Analytical grade NH4F, (NH4)2SO4, and C2H2O4·2H2O were added in a mass ratio of 1:2:3, with 20g, 40g, and 60g of each added respectively. 400g of deionized water was added, and the mixture was placed on a constant temperature magnetic stirrer. The temperature was raised to 50℃ and stirred thoroughly. The mixture was then allowed to stand at room temperature for 48h. After that, the glass was placed in the mixture for chemical etching at a temperature of 35℃ for 10min.

[0027] A Ti adhesion barrier layer and a Cu seed layer were prepared on a glass TGV through-hole sample by sputtering. The thickness of the Ti adhesion barrier layer inside the hole was 300 nm, and the thickness of the Cu seed layer was 2 μm. The pretreated glass was then metallized using electroplating. The copper plating solution composition and content were: 40 g / L Cu. 2+ 60 g / L H2SO4, 50 ppm Cl 3 mL / L SFT_A, 10 mL / L SFT_S, 5 mL / L SFT_L; the current density is controlled at 0.18 A dm³ during electroplating. -2 Electroplating time was 30 minutes, then the current density was adjusted to 0.25 A dm. -2 The reprocessing time is 90 minutes.

[0028] Example 2 A method for surface treatment of glass includes the following steps: Preparation of the glass substrate: The mass percentages of SiO2: 85%; Al2O3: 2%; B2O3: 12%; Na2O: 4.5%; SnO2: 0.2% were used. Quartz sand, alumina, boron oxide, and tin oxide were weighed and uniformly mixed to obtain a homogeneous batch. The batch was then transferred to a platinum crucible of approximately 1500 ml and placed in a high-temperature furnace with a silicon molybdenum rod. The temperature was gradually increased to 1650℃ and held for 6 hours, with stirring to accelerate the removal of glass bubbles. After melting, the molten liquid was poured into a heat-resistant stainless steel mold for shaping. The glass block was then removed and transferred to a box annealing furnace for heat treatment at 600℃ for 4 hours, followed by natural cooling to room temperature to obtain the base glass. The glass block was cut, ground, and polished to prepare samples of 20 mm × 5 mm × 1 mm.

[0029] Laser-induced etching of through-holes: The glass sample was irradiated with a laser beam of E=55uJ / pulse, pulse width τ=16ps, and repetition frequency f=500kHz. The modified glass sample was then immersed in a 5% HF acid solution and ultrasonically bathed at 30℃ for 30 min, followed by rinsing with deionized water for 5 min.

[0030] Pretreatment before metallization: Analytical grade NH4F, (NH4)2SO4, and C2H2O4·2H2O were added in a mass ratio of 1:4:6, with 10g, 40g, and 60g of each added respectively. 400g of deionized water was added, and the mixture was placed on a constant temperature magnetic stirrer. The temperature was raised to 50℃ and stirred thoroughly. The mixture was then allowed to stand at room temperature for 48h. After that, the glass was placed in the mixture for chemical etching at a temperature of 35℃ for 10min.

[0031] A Ti adhesion barrier layer and a Cu seed layer were prepared on a glass TGV through-hole sample by sputtering. The thickness of the Ti adhesion barrier layer inside the hole was 300 nm, and the thickness of the Cu seed layer was 2 μm. The pretreated glass was then metallized using electroplating. The copper plating solution composition and content were: 40 g / L Cu. 2+ 60 g / L H2SO4, 50 ppm Cl 3 mL / L SFT_A, 10 mL / L SFT_S, 5 mL / L SFT_L; the current density is controlled at 0.18 A dm³ during electroplating. -2 Electroplating time was 30 minutes, then the current density was adjusted to 0.25 A dm. -2 The reprocessing time is 90 minutes.

[0032] The only difference between Example 2 and Example 1 is that NH4F, (NH4)2SO4, and C2H2O4·2H2O are added in a mass ratio of 1:4:6, with 10g, 40g, and 60g added respectively.

[0033] Example 3 A method for surface treatment of glass includes the following steps: Preparation of the glass substrate: The mass percentages of SiO2: 85%; Al2O3: 2%; B2O3: 12%; Na2O: 4.5%; SnO2: 0.2% were used. Quartz sand, alumina, boron oxide, and tin oxide were weighed and uniformly mixed to obtain a homogeneous batch. The batch was then transferred to a platinum crucible of approximately 1500 ml and placed in a high-temperature furnace with a silicon molybdenum rod. The temperature was gradually increased to 1650℃ and held for 6 hours, with stirring to accelerate the removal of glass bubbles. After melting, the molten liquid was poured into a heat-resistant stainless steel mold for shaping. The glass block was then removed and transferred to a box annealing furnace for heat treatment at 600℃ for 4 hours, followed by natural cooling to room temperature to obtain the base glass. The glass block was cut, ground, and polished to prepare samples of 20 mm × 5 mm × 1 mm.

[0034] Laser-induced etching of through-holes: The glass sample was irradiated with a laser beam of E=55uJ / pulse, pulse width τ=16ps, and repetition frequency f=500kHz. The modified glass sample was then immersed in a 5% HF acid solution and ultrasonically bathed at 30℃ for 30 min, followed by rinsing with deionized water for 5 min.

[0035] Pretreatment before metallization: Analytical grade NH4F, (NH4)2SO4, and C2H2O4·2H2O were added in a mass ratio of 3:4:6, with 30g, 40g, and 60g of each added respectively. 400g of deionized water was added, and the mixture was placed on a constant temperature magnetic stirrer. The temperature was raised to 50℃ and stirred thoroughly. The mixture was then allowed to stand at room temperature for 48h. After that, the glass was placed in the mixture for chemical etching at a temperature of 35℃ for 10min.

[0036] A Ti adhesion barrier layer and a Cu seed layer were prepared on a glass TGV through-hole sample by sputtering. The thickness of the Ti adhesion barrier layer inside the hole was 300 nm, and the thickness of the Cu seed layer was 2 μm. The pretreated glass was then metallized using electroplating. The copper plating solution composition and content were: 40 g / L Cu. 2+ 60 g / L H2SO4, 50 ppm Cl 3 mL / L SFT_A, 10 mL / L SFT_S, 5 mL / L SFT_L; the current density is controlled at 0.18 A dm³ during electroplating. -2 Electroplating time was 30 minutes, then the current density was adjusted to 0.25 A dm. -2 The reprocessing time is 90 minutes.

[0037] The only difference between Example 3 and Example 1 is that NH4F, (NH4)2SO4, and C2H2O4·2H2O are added in a mass ratio of 3:4:6, with 30g, 40g, and 60g added respectively.

[0038] Example 4 A method for surface treatment of glass includes the following steps: Preparation of glass substrate: The mass percentages of SiO2: 61.65%; Al2O3: 14.25%; B2O3: 14.25%; MgO: 1.97%; CaO: 5.65%; SrO: 2.76%; BaO: 0.68%; CeO2: 0.1%; SnO2: 0.1%. Quartz sand, alumina, boron oxide, and tin oxide were weighed and uniformly mixed to obtain a homogeneous batch. The batch was then transferred to a platinum crucible of approximately 1500 ml and placed in a high-temperature furnace with a silicon molybdenum rod. The temperature was gradually increased to 1650℃ and held for 6 hours, with stirring to accelerate the removal of glass bubbles. After melting, the molten liquid was poured into a heat-resistant stainless steel mold for shaping. The glass block was then removed and transferred to a box annealing furnace for heat treatment at 600℃ for 4 hours, followed by natural cooling to room temperature to obtain the base glass. The glass block was cut, ground, and polished to prepare samples of 20 mm × 5 mm × 1 mm.

[0039] Laser-induced etching of through-holes: The glass sample was irradiated with a laser beam of E=55uJ / pulse, pulse width τ=16ps, and repetition frequency f=500kHz. The modified glass sample was then immersed in a 5% HF acid solution and ultrasonically bathed at 30℃ for 30 min, followed by rinsing with deionized water for 5 min.

[0040] Pretreatment before metallization: Analytical grade NH4F, (NH4)2SO4, and C2H2O4·2H2O were added in a mass ratio of 1:2:3, with 20g, 40g, and 60g of each added respectively. 400g of deionized water was added, and the mixture was placed on a constant temperature magnetic stirrer. The temperature was raised to 50℃ and stirred thoroughly. The mixture was then allowed to stand at room temperature for 48h. After that, the glass was placed in the mixture for chemical etching at a temperature of 35℃ for 10min.

[0041] A Ti adhesion barrier layer and a Cu seed layer were prepared on a glass TGV through-hole sample by sputtering. The thickness of the Ti adhesion barrier layer inside the hole was 300 nm, and the thickness of the Cu seed layer was 2 μm. The pretreated glass was then metallized using electroplating. The copper plating solution composition and content were: 40 g / L Cu. 2+ 60 g / L H2SO4, 50 ppm Cl 3 mL / L SFT_A, 10 mL / L SFT_S, 5 mL / L SFT_L; the current density is controlled at 0.18 A dm³ during electroplating. -2 Electroplating time was 30 minutes, then the current density was adjusted to 0.25 A dm. -2 The reprocessing time is 90 minutes.

[0042] The only difference between Example 4 and Example 1 is the composition of the glass material.

[0043] Example 5 A method for surface treatment of glass includes the following steps: Preparation of glass substrate: The mass percentages of SiO2: 61.65%; Al2O3: 14.25%; B2O3: 14.25%; MgO: 1.97%; CaO: 5.65%; SrO: 2.76%; BaO: 0.68%; CeO2: 0.1%; SnO2: 0.1%. Quartz sand, alumina, boron oxide, and tin oxide were weighed and uniformly mixed to obtain a homogeneous batch. The batch was then transferred to a platinum crucible of approximately 1500 ml and placed in a high-temperature furnace with a silicon molybdenum rod. The temperature was gradually increased to 1650℃ and held for 6 hours, with stirring to accelerate the removal of glass bubbles. After melting, the molten liquid was poured into a heat-resistant stainless steel mold for shaping. The glass block was then removed and transferred to a box annealing furnace for heat treatment at 600℃ for 4 hours, followed by natural cooling to room temperature to obtain the base glass. The glass block was cut, ground, and polished to prepare samples of 20 mm × 5 mm × 1 mm.

[0044] Laser-induced etching of through-holes: The glass sample was irradiated with a laser beam of E=55uJ / pulse, pulse width τ=16ps, and repetition frequency f=500kHz. The modified glass sample was then immersed in a 5% HF acid solution and ultrasonically bathed at 30℃ for 30 min, followed by rinsing with deionized water for 5 min.

[0045] Pretreatment before metallization: Analytical grade NH4F, (NH4)2SO4, and C2H2O4·2H2O were added in a mass ratio of 1:4:6, with 10g, 40g, and 60g of each added respectively. 400g of deionized water was added, and the mixture was placed on a constant temperature magnetic stirrer. The temperature was raised to 50℃ and stirred thoroughly. The mixture was then allowed to stand at room temperature for 48h. After that, the glass was placed in the mixture for chemical etching at a temperature of 35℃ for 10min.

[0046] A Ti adhesion barrier layer and a Cu seed layer were prepared on a glass TGV through-hole sample by sputtering. The thickness of the Ti adhesion barrier layer inside the hole was 300 nm, and the thickness of the Cu seed layer was 2 μm. The pretreated glass was then metallized using electroplating. The copper plating solution composition and content were: 40 g / L Cu. 2+ 60 g / L H2SO4, 50 ppm Cl 3 mL / L SFT_A, 10 mL / L SFT_S, 5 mL / L SFT_L; the current density is controlled at 0.18 A dm³ during electroplating. -2 Electroplating time was 30 minutes, then the current density was adjusted to 0.25 A dm. -2 The reprocessing time is 90 minutes.

[0047] The only difference between Example 5 and Example 4 is that NH4F, (NH4)2SO4, and C2H2O4·2H2O are added in a mass ratio of 1:4:6, with 10g, 40g, and 60g added respectively.

[0048] Example 6 A method for surface treatment of glass includes the following steps: Preparation of glass substrate: The mass percentages of SiO2: 61.65%; Al2O3: 14.25%; B2O3: 14.25%; MgO: 1.97%; CaO: 5.65%; SrO: 2.76%; BaO: 0.68%; CeO2: 0.1%; SnO2: 0.1%. Quartz sand, alumina, boron oxide, and tin oxide were weighed and uniformly mixed to obtain a homogeneous batch. The batch was then transferred to a platinum crucible of approximately 1500 ml and placed in a high-temperature furnace with a silicon molybdenum rod. The temperature was gradually increased to 1650℃ and held for 6 hours, with stirring to accelerate the removal of glass bubbles. After melting, the molten liquid was poured into a heat-resistant stainless steel mold for shaping. The glass block was then removed and transferred to a box annealing furnace for heat treatment at 600℃ for 4 hours, followed by natural cooling to room temperature to obtain the base glass. The glass block was cut, ground, and polished to prepare samples of 20 mm × 5 mm × 1 mm.

[0049] Laser-induced etching of through-holes: The glass sample was irradiated with a laser beam of E=55uJ / pulse, pulse width τ=16ps, and repetition frequency f=500kHz. The modified glass sample was then immersed in a 5% HF acid solution and ultrasonically bathed at 30℃ for 30 min, followed by rinsing with deionized water for 5 min.

[0050] Pretreatment before metallization: Analytical grade NH4F, (NH4)2SO4, and C2H2O4·2H2O were added in a mass ratio of 3:4:6, with 30g, 40g, and 60g of each added respectively. 400g of deionized water was added, and the mixture was placed on a constant temperature magnetic stirrer. The temperature was raised to 50℃ and stirred thoroughly. The mixture was then allowed to stand at room temperature for 48h. After that, the glass was placed in the mixture for chemical etching at a temperature of 35℃ for 10min.

[0051] A Ti adhesion barrier layer and a Cu seed layer were prepared on a glass TGV through-hole sample by sputtering. The thickness of the Ti adhesion barrier layer inside the hole was 300 nm, and the thickness of the Cu seed layer was 2 μm. The pretreated glass was then metallized using electroplating. The copper plating solution composition and content were: 40 g / L Cu. 2+ 60 g / L H2SO4, 50 ppm Cl 3 mL / L SFT_A, 10 mL / L SFT_S, 5 mL / L SFT_L; the current density is controlled at 0.18 A dm³ during electroplating. -2 Electroplating time was 30 minutes, then the current density was adjusted to 0.25 A dm. -2 The reprocessing time is 90 minutes.

[0052] The only difference between Example 6 and Example 4 is that NH4F, (NH4)2SO4, and C2H2O4·2H2O are added in a mass ratio of 3:4:6, with 30g, 40g, and 60g added respectively.

[0053] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that no pretreatment before metallization is performed; all other processes are exactly the same.

[0054] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that no pretreatment before metallization is performed; the rest of the processes are exactly the same.

[0055] To compare the effects of the present invention, the performance of the finished products of the above embodiments was tested. Specifically, a roughness test was conducted: the surface and the inner wall roughness of the cross-section were characterized using a white light interferometer; a cross-cut test was conducted: according to the national standard GB / T9286-1998, 10×10 small grids of 1mm×1mm were drawn on the surface of the test sample using a cross-cut knife, and the area of ​​film peeling was observed using a microscope.

[0056] The performance parameters of each embodiment and comparative example are shown in Table 1 below: Table 1

[0057] As shown in Table 1 above, in Examples 1-3 and 4-6, with the increase of ammonium fluoride content, the amount of hydrofluoric acid, the effective corrosion factor generated by its reaction with oxalic acid, continuously increases within a certain range. The glass chemical etching reaction continues, resulting in a nanoscale surface structure morphology and effectively improving adhesion. In contrast, Comparative Examples 1-2, without metallization pretreatment, exhibit significantly poor adhesion. Therefore, the method of this invention can effectively improve the adhesion of glass substrate surfaces.

[0058] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of protection of the present invention.

Claims

1. A method for surface treatment of glass, characterized in that, Includes the following steps: (1) Laser-induced treatment: Laser-induced treatment of glass is performed by using pulsed lasers to induce deformation in the glass. (2) Etching process: The glass after laser-induced treatment was etched with an etching solution to create through holes for later use. (3) Pretreatment before metallization: The etched glass is immersed in a pretreatment solution for surface treatment, during which the solution temperature is controlled at 25~50℃. After the reaction treatment is 1~20 minutes, it is taken out for use. (4) Sputtering treatment: The glass surface after step (3) was prepared by sputtering to deposit a Ti adhesion barrier layer and a Cu seed layer. (5) Electroplating treatment: The glass surface after step (4) is metallized by electroplating.

2. The surface treatment method for glass according to claim 1, characterized in that, The glass is either alkali-containing glass or alkali-free glass.

3. The surface treatment method for glass according to claim 2, characterized in that, The alkali glass contains the following components in the corresponding weight percentages: SiO2: 80-85%; Al2O3: 1.7-2.5%; B2O3: 11.1-14.5%; Na2O: 0.5-5%; and clarifier: 0-2%.

4. The surface treatment method for glass according to claim 2, characterized in that, The alkali-containing glass contains the following components in the corresponding weight percentages: SiO2: 60-65%; Al2O3: 16-17.5%; B2O3: 11.1-14.5%; MgO: 1-2%; CaO: 3-6%; SrO: 1~3%; BaO: 0.5~1%; clarifying agent: 0~2%.

5. The surface treatment method for glass according to claim 1, characterized in that, The energy of the pulsed laser mentioned in step (1) is 50uJ~100uJ.

6. The surface treatment method for glass according to claim 1, characterized in that, The etching solution used in step (2) is HF acid or KOH solution. The mass fraction of the solute in the etching solution is controlled at 3% to 50%, the etching temperature is controlled at 25 to 85°C, and the etching time is controlled at 10 to 600 min. After etching, the glass is rinsed with deionized water for 3 to 5 min.

7. The surface treatment method for glass according to claim 1, characterized in that, The pretreatment solution mentioned in step (3) is made by mixing ammonium fluoride, ammonium sulfate and oxalic acid in a mass ratio of 1:1~5:2~6. The mass concentration of the solute in the pretreatment solution is 20~40%. After the pretreatment solution is prepared, it needs to be aged at room temperature for 40~50 hours before use.

8. The surface treatment method for glass according to claim 1, characterized in that, After the glass undergoes the pretreatment described in step (3), its surface roughness is 200~600nm and its internal roughness is 200~600nm, forming a micro-nano structure.

9. A surface treatment method for glass according to claim 1, characterized in that, The glass processed by this method can be used in the fields of glass adapter boards and glass chips.